Analisis Neraca Air Sub Das Martapura - Febry Asthia Miranti; Meireinda Rahmadania (Jurnal Teknologi Berkelanjutan, 2021)
Martapura River is a river that crosses Banjar Regency and Banjarmasin City which is included in the watershed. This river empties into the Barito River, whose upstream is the junction between the Riam Kiwa River and the Riam Kanan River. Sub-watershed E is part of the Martapura watershed. The water balance is an analysis of the results of the approach to the values of hydrological processes that occur in the field. The Water Balance method is used to compare availability of water with the existing water needs. The purpose of this research is the availability of a water balance calculation that can be used as a basis for generating the concept of the water allocation in the form of an annual water supply plan. Analysis of water availability is based on the calculation of the base flow rate calculated by FJ Mock. The results of the calculation of the water balance in the dry year (80%) experienced a surplus.